Analysis of honey pollen content produced by Apis mellifera L. (Hymenoptera: Apidae) at Tabasco State, Mexico - Castellanos-Potenciano, Blanca Patricia; Ramírez Arriaga, Elia; Zaldivar-Cruz, Juan Manuel (Instituto de Ecología, A.C., 2012)
We studied 40 honey samples from Tabasco State, Mexico with melissopalynology methods. Pollen grains of 29 taxa were important (>=10%): Avicennia germinans (Acanthaceae); Borreria verticillata (Rubiaceae); Bursera simaruba (Burseraceae); Cecropia obtusifolia (Moraceae); Coccoloba aff. diversifolia (Polygonaceae), Conocarpus sp. (Combretaceae), Rumex sp. 1(Polygonaceae), Eleocharis sp. 1 (Cyperaceae); Eragrostis sp. (Poaceae), Asteraceae sp. 1 y sp. 2. (Asteraceae), Andira (Fabaceae), Diphysa carthagenensis (Fabaceae), Erythrina (Fabaceae), Haematoxylum campechianum(Fabaceae), Heliocarpus appendiculatus (Tiliaceae), Machaerium sp. (Fabaceae); Mimosa albida (Fabaceae); Mimosa pigra var.berlandieri (Fabaceae); Phyla nodiflora (Verbenaceae); Piper sp. 1, sp. 2 y sp. 3.(Piperaceae), Quercus oleoides (Fagaceae); Spondias mombin (Anacardiaceae); Spondias radlkoferi (Anacardiaceae); Cocos nucifera (Arecaceae), Muntingia calabura (Elaeocarpaceae) y Zeamays (Poaceae). In general, 14 monofloral, 7 bifloral and 19 multifloral honey samples were characterized. Most samples contained from 20,000 to 100,000 pollen grains per ten grams of honey. According to ecological parameters, homogeneous resource exploitation was registered with high diversity indexes and heterogeneous forage behavior matched with low H’ values. We registered significant correlationships between some localities by the presence of Mimosa albida, Bursera simaruba and Cecropia obtusifolia.